Fixation stability and stress redistribution following metal block use in opening-wedge high tibial osteotomy: a finite element analysis - Nha, Kyung-Wook; Kim, Hyungsuh; Song, Jae-Gwang; Hong, Hyongtaek; Kang, Kyoung-Tak; Park, Hyung Jun (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMedial opening wedge high tibial osteotomy (OWHTO) is a widely performed procedure for correcting varus malalignment and alleviating medial compartment osteoarthritis. Metal block augmentation has been proposed to enhance construct stability by reducing micromotion and stress at the osteotomy site. However, its biomechanical effects under lateral hinge fracture (LHF) and across different osteotomy techniques (uniplanar vs. biplanar osteotomy) remain poorly understood.MethodsA finite element model of the proximal tibia was constructed using the computed tomography data of a 62-year-old woman. Simulations were conducted under uniplanar and biplanar osteotomy configurations, with and without a 12 mm metal block augmentation. The LHF was modeled for three Takeuchi fracture types, in addition to the intact condition. Each model was evaluated under axial loading to quantify micromotion, peak stress at the D-hole, mean stress at the lateral hinge, and stress distribution in the locking plate and the proximal tibia.ResultsMetal block augmentation significantly improved the fixation stability across all OWHTO configurations. In the uniplanar models, the micromotion was reduced by over 90% in both the non-fracture and Type I LHF conditions, whereas the reduction ranged from 84% to 91% in the biplanar models. The peak stress around the D-hole decreased by 14%–21% in constructs with a metal block compared to those without. However, the mean plate stress increased substantially by 87% in the uniplanar model and 237% in the biplanar model. In contrast, the proximal tibial bone stress consistently decreased by 21%–28%.ConclusionMetal block augmentation improved the biomechanical stability in OWHTO constructs, with greater grains in uniplanar osteotomies and LHF models. This enhancement was accompanied by altered stress distribution, characterized by increased stress on the plate and reduced stress in the proximal tibia, suggesting a potential stress-shielding effect. By quantifying these effects under various conditions, this study provides biomechanical evidence for the selective application of metal block augmentation in clinical practice.